Efusi Pleura: Literature Review - Supriantarini, Dita; Afifah, Fiza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pleural effusion is an abnormal accumulation of fluid in the pleural space, which is the thin cavity between the pleural layers that surround the lungs. Globally, around 1.5 million patients are diagnosed each year, with the main causes being congestive heart failure, malignancy, and infection. The purpose of this article is to determine pleural effusion: a literature study. The method used is a literature review using several database journals taken from Google Scholar. Relevant keywords related to the title of the article are used in the search strategy. The results of the literature study obtained that pleural effusion is classified into transudate and exudate. The diagnosis of pleural effusion is made through anamnesis and physical examination. In addition, there are supporting examinations consisting of chest x-ray, chest ultrasound, chest CT scan, and pleural fluid analysis. Management in dealing with pleural effusion through pleural puncture (thoracentesis), thoracoscopy, conservative management (if the fluid is small), installation of water seal drainage, pleurodesis, complications and prognosis. In conclusion, pleural effusion can be diagnosed in 2 ways and by carrying out other supporting examinations.